Implication of Conversation in Interactive Dialogue of Public Eyes in Trans 7 - Aziz Rio Kausar; Kasmantoni Kasmantoni; Bustomi Bustomi (Yayasan Karinosseff Muda Indonesia, 2022)
The phenomenon of implicature is also found in many television programs, such as talk shows, comedy programs, and programs with the concept of motivating listeners or viewers . This research is only about the implicatures of conversation in the interactive dialogue of mata najwa with public officials at Trans7. The problem in this research is how is the function of conversational implicature in the interactive dialogue of Mata Najwa in Trans7. The goal to be achieved in this study is to describe how the function of conversational implicatures in the interactive dialogue between Mata Najwa and Public Officials in Trans7. This research is a research with descriptive qualitative method . Data collection is done by recording and note-taking techniques. Data analysis was carried out through several procedures: (1) data reduction (data selection and data coding), (2) data presentation, and (3) conclusion drawing and data verification . Based on the results of data analysis and discussion, the conclusion of this study the researchers found the function of conversational implicatures in the interactive dialogue of Mata Najwa Trans7 with public officials. The four implicature functions in the form of speech acts are the conversational implicature function in representative speech, the conversational implicature function in commissive speech, the conversational implicature function in directive speech, and conversational implicature in expressive speech. In addition, the researcher also found the meanings of conversational implicatures contained in Mata Najwa Trans7's interactive dialogue with public officials, there were (17) seventeen implicature intentions. These purposes include: 1) stating, 2) explaining, 3) speculating, 4) showing, 5) informing, 6) admitting, 7) giving testimony, 8) reporting, 9) refusing, 10) inviting, 11) urged, 12) suggested, 13) forbade, 14) pleaded, 15) criticized, 16) blamed, 17) insinuated. The most common conversational implicatures in Mata Najwa Trans7's interactive dialogue are conversational implicatures in the representative speech function with a total of 26 utterances. The meaning that appears the most is the intention ( state ).